Synthesis of Benzimidazole-sugar Derivatives: a Potential Treatment for Alzheimer’s Disease - YUKSEKDANACI, Seda; ASTLEY, Demet; SENTURK, Murat (Studia Universitatis Babeș-Bolyai Chemia, 2023)
In this study, a new series of chiral benzimidazole-glycosyl thiourea derivatives (5-10) were synthesized and evaluated for their inhibitory effects against hCA I, hCA II, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The structures of the benzimidazole-glycosyl thiourea compounds were determined by FTIR, 1H-NMR, 13C-NMR and elemental analysis. The KI values for the CA isoenzymes of the synthesized materials ranged from 6.03 to 42.98 nM. KI values for cholinesterase enzymes were shown to be between 5.32 and 39.14 nM. It was observed that compound 10 is the best hCA I inhibitor (KI:6.03 nM), compund 9 is the best hCAII inhibitor (KI:17.29 nM) and compound 8 is the best AChE (KI:5.32 nM) and the best BChE (KI:18.73 nM) inhibitor.